PENINGKATAN USAHA TELUR ASIN ASAP - Wara Pratitis Suprayogi; Nur Her Riyadi Parnanto (UII, 2015)
Smoke salted egg production business now stands at Karanganyar where production capacity is still low. The problem faced are the continuity of supply of duck eggs, the smoker tools that low capacity and no have of P-IRT permits. Increased smoke salted eggs can be carried out by 1) interlacement partnerships with suppliers duck eggs, 2) facilitating the permitting P-IRT, 3) introduction of appropriate technology smoker salted eggs and 4) mentoring. The activities that have been carried out to increase the impact of smoke where the salted egg business continuity and increased production capacity, expansion of marketing and revenue enhancement partner SMEs. Keywords: salted smoked, fumigation technology, production